Aplicación de Inteligencia Artificial en un Videojuego Serio para la Rehabilitación de la Articulación del Codo - Aguilar Jiménez, Diana Leticia; Santana Franco, Edith Marlene; Villarreal Carrillo, Agustín; Aguilar Figueroa , Isaac René (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The elbow joint is key in the functionality of the upper limbs and is used in many activities. In this sense, different pathologies and trauma can affect the Range Of Motion (ROM) and limit the patient’s capabilities such as playing sports, eating, drinking, brushing teeth, among others. Due to the problems described above, we have designed a prototype video game in Python, which is controlled by flexion and extension movements of the elbow. To develop it, we used OpenCV library and Mediapipe framework. The first one oversees image processing that helped us with the registration of the patient's movements in real time by means of the webcam. The final game can be used as a tool to ease the patient rehabilitation exercises.